2013
DOI: 10.1177/1359105312474915
|View full text |Cite
|
Sign up to set email alerts
|

Managing multiple goals during fertility treatment: An interpretative phenomenological analysis

Abstract: This study investigated how men and women made sense of multiple goals during fertility treatment. Both members of three heterosexual couples participated in two or three semi-structured interviews over 6 months, producing 14 accounts, which were analysed using interpretative phenomenological analysis. The goal of biological parenthood dominates assumptions in infertility research, but its importance varied between participants, who balanced that goal with retaining emotional well-being, avoiding financial dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…The results of a discrete choice experiment in Dutch and Belgian fertility clinics suggested that patients were willing to trade-off a higher pregnancy rate for more patient-centered care from physicians [29]. Scheduling and attending a consultation with an RS is just one of many family-building decisions patients and their partners will make if they proceed through fertility treatments, and in those subsequent decisions patients and their partners must balance their parenthood goals with other simultaneous and sometimes competing priorities, as also demonstrated in previous qualitative work [18]. The RS’s treatment recommendations must take into account patient and partner values and priorities along with their health history and test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a discrete choice experiment in Dutch and Belgian fertility clinics suggested that patients were willing to trade-off a higher pregnancy rate for more patient-centered care from physicians [29]. Scheduling and attending a consultation with an RS is just one of many family-building decisions patients and their partners will make if they proceed through fertility treatments, and in those subsequent decisions patients and their partners must balance their parenthood goals with other simultaneous and sometimes competing priorities, as also demonstrated in previous qualitative work [18]. The RS’s treatment recommendations must take into account patient and partner values and priorities along with their health history and test results.…”
Section: Discussionmentioning
confidence: 99%
“…The three groups were more similar than different in terms of their reasons for pursuing parenthood, with respondents overwhelmingly endorsing a core “triad” of reasons to pursue parenthood: giving love, receiving love, and added enjoyment/fun in life. A phenomenological analysis of three couples over six months after beginning treatment with in vitro fertilization found that couples balanced their main goal of achieving parenthood with four other goals: biological parenthood, retaining emotional well-being, remaining financially secure, and maintaining good relationships with partners [18]. Finally, Thompson et al found that in 37 couples seeking infertility treatment, both partners reported placing similar levels of importance on reaching the goal of parenthood [19].…”
Section: Introductionmentioning
confidence: 99%
“…When explaining their strategy selection, participants referred to their longer-term aims and goals, of which parenthood and biological parenthood was just one, reflecting the way that people in fertility treatment manage multiple goals (Phillips et al, 2014). Their strategy selection was also informed by the link they perceived between stress and infertility, so that they attempted to control the pressure and stress they experienced in order to improve their chances of conception.…”
Section: Discussionmentioning
confidence: 99%
“…The self-regulation model (SRM) focuses on how individuals attempt to attain their goals through the cycle of evaluation, coping strategy selection, re-evaluation and adjustment (Carver, Scheier, & Fulford, 2008). A self-regulatory framework has previously helped to understand how people managed multiple goals during treatment for infertility (Phillips, Elander, & Montague, 2014), and in this study we applied the same conceptual framework to participants' experiences of coping strategy selection during their first six months undergoing in vitro fertilisation (IVF) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…El Kissi et al (2014) found greater emotional maladjustment, emotional disturbances, and worse quality of life in infertile couples compared to general population. Also, variables such as coping strategies and alexithymia were analyzed with an interest in their relationship with the emotional distress experienced in infertility (Phillips, Elander, & Montague, 2014;Shi, Wu, & Zhu, 2006).…”
mentioning
confidence: 99%